PERAN GURU DI MASA DEPAN : TELAAH KRITIS DALAM PERSPEKTIF PEDAGOGIK FUTURISTIK - Fauziyah, Syifa Hasna; Herlambang, Yusuf Tri; Muhtar, Tatang (UIN Sumatera Utara Medan, 2024)
To produce quality human resources, it is necessary to have policies that prioritize education as an investment in the future. The challenge in facing future education is to prepare human resources who are able to face problems and compete in the global market through futuristic education as an effort to equip humans in the future. However, education is currently in a chaotic condition so it is feared that it can hinder human differences. The purpose of this study is to describe or explain the results of literature studies on the role of teachers in the future according to futuristic pedagogic views. In the results of the discussion, future education requires teachers who have future insight and are critically aware to produce a better life. The role of teachers in the future is also as a transformer, namely being a pioneer of change in education, having a personal, social, political, and theoretical approach and having a Growth-Mindset thinking. It is hoped that with this role, teachers can prepare students to face future challenges and have the skills of critical thinking and problem solving, communication, collaboration, creativity and innovation, leadership and spirited entrepreneurship, as well as digital literacy.